Efektivitas Pendekatan Kontekstual Pada Pembelajaran IPS di SD/MI - Windy Audia; Rahmawati Rahmawati; Oman Farhurohman (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research aims to determine the effectiveness of contextual learning approaches in subjects. Social Sciences (IPS) in Elementary Schools/Madrasah Ibtidaiyah based on literature review. The contextual learning approach is considered relevant because it allows students to connect lesson material with everyday life experiences, thereby improving students' understanding and critical thinking skills. The method used in this research is a literature study, where researchers collect and analyze various literature sources related to contextual learning and its application in social studies learning. These sources include books, scientific journals, and previous research that supports contextual learning theory and practice. The results of the literature review show that a contextual learning approach can increase student engagement, understanding of the material, as well as critical and analytical thinking skills. The contextual learning approach, based on evidence from the reviewed literature, is effective in improving learning outcomes and student involvement in social studies learning in SD/MI. Thus, this approach can be one of the recommended learning strategies to improve the quality of education in elementary schools.